Activation of GLP-1R modulates the spontaneous discharge of nigral dopaminergic neurons and motor behavior in mice with chronic MPTP Parkinson's disease - Liu, Wen-Hong; Liu, Cui; Xue, Yan; Sun, Xiang-Rong; Chen, Xin-Yi; Chen, Lei (Frontiers in Aging Neuroscience, 2025)
The gradual decline of nigral dopaminergic neurons is the main cause of Parkinson's disease (PD), yet as of now, there exists no conclusive therapeutic intervention. Glucagon-like peptide-1 (GLP-1) is an incretin, which is also a key substance regulating neuronal activity and synaptic transmission. GLP-1 receptors (GLP-1Rs) are widely expressed in the central nervous system. Chronic administration of low doses of 1-methyl-4-phenyl, 1,2,3,6-tetrahydropiridine (MPTP) mitigates mortality in mice during the modeling phase, thereby more closely mirroring the progression of PD. This study aims to observe the effects of GLP-1 receptor agonists (GLP-1RAs) on the firing activity of nigral dopaminergic neurons and motor behaviors in MPTP-induced chronic PD mice. Our findings revealed that peripheral administration of GLP-1RAs exendin-4 significantly alleviated motor impairments in MPTP-induced chronic PD mice. Concurrently, peripheral administration of exendin-4 increased the number of active dopaminergic neurons, improved the spontaneous firing activity, as well as alleviated MPTP-induced dopaminergic neuron loss in MPTP-induced PD mice. Furthermore, local administration of exendin-4 directly increased the firing rate of nigral dopaminergic neurons via GLP-1Rs, suggesting that peripheral administration of exendin-4 may exert neuroprotection through its mild excitation on dopaminergic neurons. These findings collectively imply that peripheral administration of GLP-1RAs may hold potential in the treatment of PD.